Karakteristik Psikometrik Alat Ukur Kualitas Hidup bagi Pasien Hipertensi: Tinjauan Sistematis - Afif Rakha Murtadha; Tri Murti Andayani; Dwi Endarti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Hypertension is a chronic condition significantly impacting physical and psychological well-being. HRQoL instruments must undergo cross-cultural adaptation and psychometric evaluation before clinical application. Objective: This systematic review evaluated the psychometric robustness (reliability, validity, responsiveness) of hypertension-specific HRQoL instruments. Methods: Eight databases were searched for original research published in English or Indonesian (2021–2026) following PRISMA 2020. Methodological quality and evidence certainty were assessed using COSMIN and modified GRADE. Results: 13 studies from 10 countries were included. Six instruments (46.1%) demonstrated strong psychometric profiles, including adequate content validity and robust reliability. While content validity (100%) and internal consistency (84.6%) were strong due to rigorous adaptation, divergent validity and responsiveness were severely underreported (84.6%). According to COSMIN guidelines, test-retest reliability studies with sample sizes below 50 participants are considered to have 'Low' GRADE evidence quality due to insufficient precision, despite demonstrating adequate ICC values. QLICD-HY, STI-HRQoL, and DASI provided the strongest evidence. Conclusion: Instruments are generally reliable, yet future research must evaluate clinical responsiveness through longitudinal designs. Instruments with the strongest psychometric profiles, such as QLICD-HY and DASI, are recommended for accurate patient assessment.